The Effects of Color Tone on Brand Image Perception in the Hotel Industry: A Case Study of Maruay Garden Hotel - บุปผา อรัญญา; จันทร์ฉาย เพ็ญพิมพ์; วชิรกลิ่นขจร วชิรกลิ่นขจร; ดีเจริญชิตพงศ์ จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to 1) examine the process of designing brand identity for the rebranding of Maruay Garden Hotel, 2) design and develop public relations media reflecting the new brand image, and 3) evaluate brand perception and satisfaction among the target group. The sample consisted of 50 participants exposed to the rebranding media, selected through purposive sampling. Research instruments included brand identity design media and a five-point Likert scale questionnaire. Data were analyzed using mean and standard deviation. The results revealed that brand perception toward the new image (x̄= 4.52, S.D. = 0.56), attractiveness and visual design (x̄= 4.58, S.D. = 0.54), and overall satisfaction (x̄= 4.50, S.D. = 0.59) were at the highest level, while content understanding was at a high level (x̄= 4.46, S.D. = 0.63). The findings indicate that the rebranding media effectively enhanced brand perception and generated a high level of satisfaction among participants.